INTERRELASI BUDAYA PESERTA DIDIK DALAM PEMBELAJARAN IPS UNTUK MEWUJUDKAN HARMONISASI SOSIAL (STUDI KASUS DI SMP NEGERI 2 BANJAR AGUNG, KABUPATEN TULANG BAWANG) - Yusinta Tia Rusdiana (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2015)
Owned cultural diversity of learners is not uncommon led to disputes or different perspectives both about the accent, the character that allows the interrelation of culture of learners in the learning process so that the realization of social harmony. In this study the authors used method Descriptive Qualitative. This research shows that (1) in planning learning, teachers make learning device with a copy of the team MGMP (2) the implementation of learning social studies in the class that has the diversity already integrated but teachers do not take advantage of it by forming a class multicultural (3) form of interrelation of culture learners in learning social studies class in the form of verbal communication (Indonesian), verbal messages (words, intonation), non-verbal communication such as gestures during the learning process of students showed enthusiasm and body language. (4) the constraints faced by the class teacher is a teacher who has a diversity not understand the characteristics of students, so that students are less motivated. While the constraints faced by learners within the school are the stereotypes and etncentrism learners.